Deciphering the Effective Relationship between Reading Fluency and Comprehension (Revue El-Wahat pour les Recherches et les Etudes, 2023)
Abstract:Reading is a complex process requiring from the reader to use his background knowledge, phonemic awareness and a letter to sound correspondence, and a meaning construction from the text. The consecutive performance of all those tasks results in reading fluency. After acknowledging fluency as a key component in an effective reading comprehension, exploring this area of research has gained scholars’ attention and interest. This paper aims at investigating the correlative relation that links fluency to comprehension. To achieve the study objectives and answer the research questions, 90 second year EFL learners at the ENS of Constantine were tested via Three Minute Reading Assessments test (3-MRA). Findings revealed a statistically significant positive correlation between students’ Correct Word per Minute and Comprehension scores. Though the degree of association between the variables was moderate; however, this cannot prevent us from concluding that improved fluency as signaled by automatic and accurate word recognition lead to improved comprehension.Keywords: Automatic and accurate word recognition; comprehension; Correlative links; EFL students; Reading fluency